Question

( begin{aligned} text { 80) } & frac{sin 24^{circ} cos 6^{circ}-sin 6^{2} sin 66^{circ}}{sin 21^{circ} cos 39^{circ}-cos 51^{circ} sin 69^{circ}} =& frac{sin 24^{circ} cos 6-sin 6^{circ} sin left(90^{circ}-24right)}{sin 21^{circ} cos 39^{circ}-cos (90-39) sin left(90^{circ}-2right)^{circ}} =& frac{sin 24^{circ} cos 6^{circ}-sin 6^{circ} cos 24^{circ}}{sin 21^{circ} cos 39^{circ}-sin 39^{circ} cos 21}=frac{sin (24-6)}{sin (21-39)} =& frac{sin 18^{circ}}{sin 18^{circ}}=-1 end{aligned} )

# sin 24° cos 6º - sin 6°sin 66° 25. The value of sin 21° cos 39º – cos51° sin 69° (A)-1 (A)-1 (B)1 (C)2 (D) none (D) none

Solution